Effortless healing : 9 simple ways to sidestep illness, shed excess weight, and help your body fix itself - Mercola, Joseph, frey50; Perlmutter, David (New York Harmony Books, 2015)
Do you have to tell your leg how to heal itself? No. Your body does this automatically, effortlessly. So why can't it "heal" excess fat? Mercola reveals the nine simple secrets to a healthier, thinner you. The results are amazing and the steps can be easy to implement.
Outlines nine keys to maximizing health, preventing disease, and protecting the body from the consequences of modern lifestyles.
Part one: Effortless health. What effortless healing is-and why you need it ; Before you begin -- Part three: Help your body fix itself -- Drink pure water ; Eat more veggies (four effortless ways to eat more) ; Burn fat for fuel ; Exercise less and gain more benefits ; Enjoy the sun and get your vitamin D ; Let your gut flourish ; Clean your brain with sleep ; Go barefoot--and other ways to stay grounded ; Avoid these six "health foods" -- Part three: Make it your own. Your effortless healing plan.
Keywords: Nutrition; Diet; Health behavior; Self-care, Health; Diet; Health behavior; Nutrition; Self-care, Health